USE OF NEW INFORMATION TECHNOLOGIES IN STUDENTS’ STUDYING OF ENGLISH LANGUAGE (Journal of Information Technologies in Education (ITE), 2013)
Particular use of new information technologies in teaching of future teachers of foreign languages; didactic possibilities of information technologies in teaching English language are described in the article.
Keywords: information technology; uses of information technologies; Internet; computer programs; online resources